Clinical psychology and people with intellectual disabilities. - Emerson, Eric (John Wiley & Sons, 2012)
Clinical Psychology & People with Intellectual Disabilities provides trainee and qualified clinical psychologists with the most up-to-date information and practical clinical skills for working with people with intellectual disabilities.-Represents an invaluable training text for those planning to work with people with intellectual disabilities -Includes coverage of key basic concepts, relevant clinical skills, and the most important areas of clinical practice -All chapters have been fully updated with the latest evidence. New chapters cover working professionally, working with people with autism and addressing aspects of the wider social context within which people with learning disabilities live.-Beneficial to related health and social care staff, including psychiatrists, nurses, and social workers.